Perception of parental support in the career development of students with intellectual disabilities - Milanovic-Dobrota, Biljana; Mentus-Kandić, Tatjana; Buha, Nataša (Specijalna edukacija i rehabilitacija, 2024)
Introduction. Parents are the primary source of advice, information, and mediation in children’s career development. For persons with intellectual disabilities, parental support is necessary during all stages of career development, and it is especially important in the period of vocational education. Objectives. The main goal of the paper was to determine how students with intellectual disabilities perceived their parents’ support during education for a chosen occupation, with special attention to some factors of the family and school environments. Methodes. The sample consisted of 155 participants with mild intellectual disability undergoing professional training in schools for students with developmental disabilities. The Career-Related Parental Support Scale was used in the research. It was designed to assess adolescent perceptions of parental support across the domains of instrumental assistance, emotional support, verbal encouragement, and career-related modeling. Results. In the sample as a whole, the participants perceived the greatest parental support in the domain of verbal encouragement and the least in career-related modeling. Greater support from their parents in career development was perceived by those who lived in a family environment with both parents, as well as those whose parents were more educated, compared to students of senior classes and those who achieved excellent results, while no differences were found in relation to the gender. Conclusion. The analysis of the obtained results indicated certain deficiencies in the field of career guidance and counseling of students with intellectual disabilities. The obtained findings point to the need to improve cooperation with students’ families in this field and empower them in relation to the ways in which they can contribute to the career success of children. Also, the necessity of expanding knowledge in the field of career development for a deeper understanding of the key problems in this field was highlighted.
Keywords: parents; support; career development; students with intellectual disabilities